2008
DOI: 10.2478/s11532-008-0044-1
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Xenbucin using Suzuki reaction catalyzed by Pd/C in water

Abstract: Xenbucin 1, an analgesic drug, was synthesized in 4 steps using two different routes. The biaryl fragment could successfully be produced via a Pd/C catalysed Suzuki coupling in water using sodium tetraphenylborate as a phenylation reagent. Overall yields of the routes were 36% and 59%, respectively. © Versita Warsaw and Springer-Verlag Berlin Heidelberg.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 8 publications
0
9
0
Order By: Relevance
“…This latter group further indicated that the oxidative addition of aryl bromides or aryl borates was the main cause for Pd leaching. Further interesting examples of Suzuki–Miyaura reactions catalyzed by Pd/C have been reported, but most developed protocols mainly focus on using active aryl halides, such as aryl iodides and bromides, to obtain non‐heterobiaryl compounds. It is still a challenge, however, to use Pd/C as catalyst for the synthesis of heterocyclic biaryl derivatives.…”
Section: Applications Of Pd/cmentioning
confidence: 99%
“…This latter group further indicated that the oxidative addition of aryl bromides or aryl borates was the main cause for Pd leaching. Further interesting examples of Suzuki–Miyaura reactions catalyzed by Pd/C have been reported, but most developed protocols mainly focus on using active aryl halides, such as aryl iodides and bromides, to obtain non‐heterobiaryl compounds. It is still a challenge, however, to use Pd/C as catalyst for the synthesis of heterocyclic biaryl derivatives.…”
Section: Applications Of Pd/cmentioning
confidence: 99%
“…In addition, the handling and removal of boron‐containing byproducts are easy when compared to other organometallic reagents, especially in a large‐scale synthesis. A number of reviews and reports have been published that enhance the tremendous use of Suzuki coupling in the C―C bond formation . Based on the above findings and in continuation of our interest in the synthesis and bioassay of different heterocyclic compounds, we herein report the synthesis, characterization, and antimicrobial activity of novel 2,4,6‐trisubstituted quinazoline derivatives.…”
Section: Introductionmentioning
confidence: 88%
“…Although, Diflunisal has been prepared in one step by Suzuki coupling, excellent yield was obtained only by using a phosphine based catalyst, glovebox and degassed water (Scheme 5) [20]. Also, Felbinac has been prepared by Suzuki coupling using either phenylboronic acid [25,26] or tetraphenylborate [5,27] as reactant (Scheme 6). Suzuki coupling with free hydroxyl or carboxylic acid functionalities present in the aromatic halide have been reported but, aryltrifluoroborates, strong bases (KO t Bu, LiOH, KF), microwave or phosphine based palladium catalysts have been utilized [28][29][30][31][32][33].…”
Section: Catalytic Preparation Of Diflunisalmentioning
confidence: 99%
“…Development of efficient phosphine free catalysts for preparation of hydrophilic substrates are of interest and reactions without a phosphine ligand, strong base and free hydroxyl groups in arylhalide have been reported recently [43,44]. As part of our ongoing projects considering synthesis of biphenyl carboxylic acids and low-molecural sized drugs employing Pd-catalysts [5,14,27,45], we have noticed that Pd/C has turned out to be a good catalyst for arylation of bromobenzoic acids [27]. Pd/C is also reported to catalyze reactions of halophenols, though in these reactions iodine is required as the halide and/or the use of microwave power for effective reactions [46,47].…”
Section: Catalytic Preparation Of Diflunisalmentioning
confidence: 99%
See 1 more Smart Citation